Shallow-focus seismic activity in the rear of Japan-Sakhalin insular arc and its possible tectonic nature - Tikhonov, I.; Lomtev, V. (Geofizicheskiy Zhurnal, 2014)
On the base of analysis of data from different seismic bulletins for the Japan Sea basin the most comprehensive unified catalogue of earthquake with magnitude M > 3,0 and depths h < 60 km for the period 1975-2010 has been prepared for the first time. Maps of epicenter of events for the four intervals (0-10, 11-20, 21-30 and 31-60 km) and three sub-latitude sections are plotted. Structural peculiarities have been considered and possible tectonic nature of seismic zone along submarine margin or borderland of the Japan-Sakhalin island arc: regional uplift, rather mega-duplex fracture of compression faults, caused by crustal sliding at the rear of frontal deep thrust.